Microcredit, Microenterprises And Social Welfare Of The Rural Poor In North-Eastern Trinidad: An Evaluation Of "Hope" - Flavius, Talia Esnard; Aziz, Zainab (Asian Academy of Management (AAM), 2011)
The study examined the relationship between microcredit, microenterprises, and the social welfare of the rural poor in north-eastern Trinidad. Guided by the main propositions of social capital theory, the researchers held 45 semi-structured interviews with active participants/clients within a case study research design. The data showed that access to microcredit through Helping Others Prosper Economically (HOPE) positively affected their microenterprises and social welfare, though marginally. Findings also revealed that fragmented social relations within the network, conflict, distrust, and the loose structure of the program limited the impact of their access to microcredit on social welfare as well as the financial potential of the lending organisation, that is, HOPE. It is the contention of this paper, therefore, that such questionable social relations dynamics 'hijack' the promise of collective social networks as exercised through goodwill and resource building. Implications of this study and directions for future research are discussed.